Emergency department boarding: a descriptive analysis and measurement of impact on outcomes. Issue 6 (5th April 2018) - Salehi, Leila; Phalpher, Prashant; Valani, Rahim; Meaney, Christopher; Amin, Qamar; Ferrari, Kiki; Mercuri, Mathew
CLINICIAN'S CAPSULE: What is known about the topic? Bed boarding is one of the major contributors to emergency department overcrowding. What did this study ask? What are the characteristics of patients with prolonged boarding times, and what are the impacts on patient-oriented outcomes? What did this study find? Patients who were older, sicker, and had isolation and telemetry requirements experienced longer boarding times, and longer inpatient length of stay even after correcting for confounders. Why does this study matter to clinicians? Organization-wide interventions to improve efficiency and flow are required to mitigate the burden of bed boarding. Abstract: Objectives: Delays in transfer of admitted patients boarded in the emergency department (ED) to an inpatient bed is a major driver of ED overcrowding. We sought to identify explanatory factors behind ED boarding as well as the impact of boarding on total inpatient length of stay (IP LOS) and inpatient mortality. Methods: We conducted a retrospective single-centre observational study during the period between January 1 and December 31, 2015 at a very high volume community hospital. All patients admitted from the ED to Medicine, Pediatrics, Surgery, and Critical Care were identified. The mean ED LOS and boarding time as well as patient-specific and institutional factors that were independently associated with prolonged ED LOS (≥24 hours) and prolonged boarding time (≥12 hours) were identified. Mean inpatient length of stay (IP LOS) and the odds of inpatient mortality were calculated for those patients with prolonged ED wait times. Results: There were 13, 872 unique admissions during the study period. Patients admitted to the Medicine service exhibited significantly higher ED wait times than other services. Within Medicine patients, there was a statistically significant greater odds of prolonged ED wait times for patients who were older, had a greater comorbidity burden, and required more specialized inpatient care. Medicine patients with prolonged boarding times also experienced a mean of 0.9 days longer IP LOS even after adjusting for confounders. Conclusion: Within our cohort, older, sicker patients and those patients requiring more resource-intensive inpatient care had the longest ED wait times. These prolonged wait times are associated with significantly increased IP LOS. RÉSUMÉ: Objectif: Les retards de mutation des patients du service des urgences (SU) à l'étage est un facteur important d'engorgement. L'étude visait donc à cerner des facteurs sous-jacents aux délais d'attente au SU avant l'hospitalisation et à évaluer l'incidence de ces délais sur la durée totale du séjour à l'hôpital et sur la mortalité chez les malades hospitalisés. Méthode: Il s'agit d'une étude d'observation, rétrospective et unicentrique, menée dans un hôpital communautaire recevant un nombre élevé de malades, entre le 1 er janvier et le 31 décembre 2015. Ont été relevés tous les dossiers des patients hospitalisés, depuis le SU, dans les services de médecine, de pédiatrie, de chirurgie et de soins intensifs. La durée moyenne de séjour au SU (DSSU) et le temps moyen d'attente avant l'hospitalisation ainsi que des facteurs propres aux patients et à l'établissement associés de manière indépendante à une DSSU prolongée (≥24 heures) et à un délai d'attente prolongé avant l'hospitalisation (≥12 heures) ont été notés. Nous avons calculé, pour les patients ayant connu un délai d'attente prolongé au SU, la durée moyenne de séjour à l'hôpital et les cotes de mortalité chez les patients hospitalisés. Résultats: Il y a eu 13 872 hospitalisations en un seul séjour durant la période à l'étude. Les patients admis au service de médecine ont connu des délais d'attente au SU significativement plus élevés que ceux admis dans d'autres services. Parmi les patients hospitalisés au service de médecine, les cotes de délai d'attente prolongé au SU étaient significativement plus élevées pour les patients âgés, pour ceux souffrant de maladies concomitantes et pour ceux ayant besoin de soins spécialisés à l'hôpital. En outre, les patients admis au service de médecine ayant connu un long délai d'attente avant l'hospitalisation ont également connu un séjour à l'hôpital plus long de 0, 9 jour en moyenne, et ce, même après rajustement des facteurs parasites. Conclusion: Les résultats de l'étude ont démontré que, au sein de la cohorte étudiée, les patients âgés, les patients les plus malades et ceux dont l'état nécessitait beaucoup de ressources à l'hôpital ont également connu les délais d'attente les plus longs au SU. D'ailleurs, ces derniers délais ont été associés à une augmentation significative de la durée de séjour à l'hôpital.